2022
DOI: 10.5737/236880763213037
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions to improve communication about sexual health between nurses and gynecologic oncology patients: A narrative review

Abstract: Despite the desire of gynecologic oncology (GO) patients to speak openly about their sexual health experience with nurses, nurses often feel ill equipped to engage in these conversations. There are very few educational interventions available to GO nurses to improve sexual health communication with patients. The purpose of this narrative review is to identify and summarize existing educational interventions in this field. A literature search conducted in three databases, for the years 2010 through 2020, identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 30 , 37 Interventions to improve communication skills about sex have shown promising results in a recently published review. 38 To facilitate discussions about possible cancer‐related impact on sex life we recommend clinical routines, including checklists, to specify when in the disease trajectory these issues should be brought up with patients, and what to include in these conversations. Such routines need to be developed for each diagnosis to fit into the current care and type of treatment plan, and reflected in guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 , 37 Interventions to improve communication skills about sex have shown promising results in a recently published review. 38 To facilitate discussions about possible cancer‐related impact on sex life we recommend clinical routines, including checklists, to specify when in the disease trajectory these issues should be brought up with patients, and what to include in these conversations. Such routines need to be developed for each diagnosis to fit into the current care and type of treatment plan, and reflected in guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies have shown that nurses and physicians inquire more knowledge and training in addressing the subject 30,37 . Interventions to improve communication skills about sex have shown promising results in a recently published review 38 . To facilitate discussions about possible cancer‐related impact on sex life we recommend clinical routines, including checklists, to specify when in the disease trajectory these issues should be brought up with patients, and what to include in these conversations.…”
Section: Discussionmentioning
confidence: 99%